THE TRANSPORTABILITY OF WESTERN PSYCHOLOGY - David L Krantz (Faculty of Psychology Universitas Gadjah Mada, 1993)
During the six months I was a Fulbright lecturer in Indonesia I became acutely aware that some topics in psychology travelled well while others did not. When I taught methodology or talkde about laboratory,